A Conceptual Model for Projecting Coccolithophorid Growth, Calcification and Photosynthetic Carbon Fixation Rates in Response to Global Ocean Change - Gafar, Natasha A.; Eyre, Bradley D.; Schulz, Kai G. (Frontiers in Marine Science, 2018)
Temperature, light and carbonate chemistry speciation all influence the growth, calcification and photosynthetic carbon fixation rates of coccolithophores to a similar degree. There have been multiple attempts to project the responses of coccolithophores to changes in carbonate chemistry, but the interaction with light and temperature remains elusive. Here we devise a simple conceptual model to derive a fit equation for coccolithophorid growth, photosynthetic carbon fixation and calcification rates in response to simultaneous changes in carbonate chemistry speciation, temperature and light conditions. The fit equation is able to account for up to 88% of the variability in measured metabolic rates. Equation projections indicate that temperature, light and carbonate chemistry speciation all have different modulating effects on both optimal growth conditions and the sensitivity of responses to extreme environmental conditions. Calculations suggest that a single extreme environmental condition (CO2, temperature, light) will reduce maximum rates regardless of how optimal the other environmental conditions may be. Thus, while the response of coccolithophores to ocean change depends on multiple variables, the one which is least optimal will have the most impact on overall rates. Finally, responses to ocean change are usually reported in terms of cellular rates. However, changes in cellular rates can be a poor predictor for assessing changes in production at the community level. We therefore introduce a new metric, the calcium carbonate production potential (CCPP), which combines the independent effects of changes in growth rate and cellular calcium carbonate content to assess how environmental changes will impact coccolith production. Direct comparison of CO2 impacts on cellular CaCO3 production rates and CCPP shows that while the former is still at 45% of its pre-industrial capacity at 1000 uatm, the latter is reduced to 10%.